Anticoccidial Vaccination Is Associated with Improved Intestinal Health in Organic Chickens - Désirée S. Jansson; Johan Höglund; Elisabeth Bagge; Tomas Jinnerot; Magne Kaldhusdal (Veterinary Sciences, 2022)
Eimeria spp. and Clostridium perfringens (CP) are pathogens associated with coccidiosis and necrotic enteritis (NE) in broiler chickens. In this study we evaluated the effect of anticoccidial vaccination on intestinal health in clinically healthy organic Ross 308 chickens. On each of two farms, one unvaccinated flock (A1 and B1) was compared to one vaccinated flock (A2 and B2) until ten weeks of age (WOA). Faecal oocysts were counted weekly, and species were identified by PCR (ITS-1 gene). Lesion scoring, CP quantification and PCR targeting the CP NetB toxin gene were performed at three, four, and six WOA and chickens were weighed. Necropsies were performed on randomly selected chickens to identify coccidiosis/NE. Oocyst shedding peaked at three WOA in all flocks. Later oocyst shedding (E. tenella/E. maxima) in unvaccinated flocks at 5–7 WOA coincided with coccidiosis/NE. Although results differed somewhat between farms, vaccination was associated with lower intestinal lesion scores, reduced caecal CP counts, lower proportions of netB-positive CP, lower body weight at three–four WOA, and similar or slightly increased body weight at six WOA. In conclusion, the intestinal health of organic broilers can benefit from anticoccidial vaccination when oocyst exposure levels are high.